2011
DOI: 10.1186/1471-2105-12-s1-s16
|View full text |Cite
|
Sign up to set email alerts
|

SOMEA: self-organizing map based extraction algorithm for DNA motif identification with heterogeneous model

Abstract: BackgroundDiscrimination of transcription factor binding sites (TFBS) from background sequences plays a key role in computational motif discovery. Current clustering based algorithms employ homogeneous model for problem solving, which assumes that motifs and background signals can be equivalently characterized. This assumption has some limitations because both sequence signals have distinct properties.ResultsThis paper aims to develop a Self-Organizing Map (SOM) based clustering algorithm for extracting bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…In contrast, Markov models can overcome this problem ( [8] pp. 110-114) and have been used in conjunction with SOM [21].…”
Section: Distance For Non-homologous Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Markov models can overcome this problem ( [8] pp. 110-114) and have been used in conjunction with SOM [21].…”
Section: Distance For Non-homologous Sequencesmentioning
confidence: 99%
“…One may use SOM to characterize these heterogeneous splice sites, quantify similarities among them, and potentially discover new type of introns. Several studies have demonstrated the values of using SOM to characterize sequence motifs [17][18][19][20][21][22], but their efforts do not seem sufficiently appreciated by biologists. Given the many advantages of SOM over conventional clustering [1], biologists should gain a new perspective on the relationship among sequence motifs through the SOM extension in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Motif discovery in DNA data sets is a challenging problem domain because of lack of understanding of the nature of the data, and the mechanisms to which proteins recognize and interact with its binding sites are still complicated to biologists [35]. If the motif is TFBS; recent studies have shown that the underlying regulatory mechanisms of TFBS are complex, dynamic (especially in higher organisms) and can be arranged in multiple hierarchical levels [43].…”
Section: Challenges Of Mining Motifsmentioning
confidence: 99%
“…Hence, a SOM-based clustering algorithm was presented in [23], in which the authors extracted binding sites in DNA sequences. The main novelty of this work was to consider two different types signals in DNA sequences, showing that treating them separably better results can be achieved.…”
Section: Artificial Intelligence-based Techniquesmentioning
confidence: 99%
“…The tool proposed a intra-node soft competitive procedure in each node model to achieve maximum discrimination of motif from background signals, by weighting two different models: position specific scoring matrix and Markov chain. As it happened in [23] and [27], this method was inserted in another SOM-based approach, called SOMBRERO [28], that constructed models for motifs that were structurally similar.…”
Section: Artificial Intelligence-based Techniquesmentioning
confidence: 99%